Risk Factors Predicting Recurrent Small Intestinal Resection for Crohn’s Disease of the Terminal Ileum - Hanna Binder; Hugh J Freeman (Canadian Journal of Gastroenterology)
This study examined potential risk factors for recurrent small intestinal resection in a ‘reagent-grade’ group of 94 consecutive patients with prior removal of histologically defined Crohn’s disease localized to the distal ileum seen by one gastroenterologist at a single teaching hospital. There were 38 males and 56 females ranging in age from 15 to 58 years, with an average length of follow-up of 8.7 years. Of these, 26% required a second resection for recurrent small intestinal disease. Cumulative reoperation rates in these 25 patients were 18% at five years and 24% at 10 years. Univariate and multivariate analyses of multiple demographic, clinical, laboratory and pathological variables revealed two apparent statistically significant independent risk factors for a second intestinal resection: steroid treatment, likely an indirect indication of more severe disease activity; and the presence of an internal fistula, consistent with the emerging concept of a relatively more aggressive clinical form of Crohn’s disease.